Indonesian Private University Students’ Entrepreneurial Intention - Pradana, Mahir; Kartawinata, Budi Rustandi (APMBA (Asia Pacific Management and Business Application), 2020)
The study focuses on the entrepreneurship education at a private business school in Indonesia due to the accelerate impact through the country economy that by implementing entrepreneurship education, one of the factors driving entrepreneurial growth in a country is the higher education institutions' role. The study took places at Telkom University, Indonesia, by surveying 458 business school students. The data analysed using a path analysis technique with SmartPLS ver. 3. Our result shows that the factors affecting entrepreneurial orientation show significant and positive effects which eventually cause a similar effect on entrepreneurial intention. Therefore, higher education institutions, especially business schools, should consider these factors as driving forces towards entrepreneurial intention. Practical implications for the development of the entrepreneurship curriculum also drawn in this study.